Using Project-Based Learning in Reading Class: Based on Students Perceptions At Junior High School Manokwari - Suardi Sahid; Riana Murianty; Hana C. S. Rumbewas (Universitas Islam Ahmad Dahlan (UIAD), 2026)
This study aimed to investigate the effectiveness of Project-Based Learning (PjBL) in improving students’ reading comprehension and to explore their perceptions toward its implementation. A mixed-methods design was employed, combining quantitative data from reading comprehension tests with qualitative data from classroom observations and student interviews. The participants were twenty-seven eighth- grade students, six of whom were selected for interviews.The quantitative results showed that the majority of students (51.85%) reached the Advanced category, with an average score of 82.22, indicating a relatively high level of comprehension. In conclusion, Project-Based Learning (PjBL) was found to be effective in enhancing students’ reading comprehension by integrating cognitive, social, and affective dimensions of learning. It transformed the reading process from teacher-centered to student-centered learning, encouraging active participation and deeper understanding. Therefore, teachers are encouraged to implement PjBL regularly with adequate scaffolding, differentiated instruction, and culturally relevant materials to ensure inclusive and meaningful literacy development.